Teaching English Vocabulary Using Total Physical Response (TPR) Method - Afrianti, Uli Ulfah; Rustipa, Katharina (Jurnal Pendidikan Bahasa Inggris undiksha, 2023)
Vocabulary is the most important part of learning a second language. Teaching vocabulary, especially for young learners, should be fun, engaging, and easy to understand. One alternative method that can be applied in class is total physical response. The purpose of the research is to analyze Teaching English Vocabulary Using the Total Physical Response (TPR) Method at elementary school. To find out the results and describe the students' difficulties, the researcher used a qualitative descriptive analysis method. To obtain qualitative information, material was taken from observations in the form of field notes, documentation, and interviews, as well as student and teacher interviews. The method of analyzing the data would be in descriptive analysis. The steps in the data analysis process are data reduction, data display, conclusion, and verification. Apart from the TPR test results, after attending the class, the average student is 80–70. It can be concluded that fourth grade students at elementary school can understand the material better and are motivated to learn using Total Physical Response (TPR), which effectively improves students' skills and control.